The implementation of e-learning web course learning in mathematics at 10th grade hospitality department - Iffah Nurfitriani; Tri Astuti Arigiyati; Irham Taufiq; Myrat Hayytjanov (Universitas Sarjanawiyata Tamansiswa, 2023)
The objectives of this study were: (1) To find differences in student mathematics learning outcomes based on the use of web course-based e-learning learning media and conventional learning in class X students majoring in Hospitality. (2) To find differences in student mathematics learning outcomes based on the level of independence in learning mathematics for class X students majoring in Hospitality. (3) To find out that there is an interaction between the use of web course learning media and the level of independence in learning mathematics for class X students majoring in Hospitality. The method used is an experimental research method. The research design used is factorial. The data analysis technique used is a two-way analysis of variance. The results of this study are: (1) there is a difference between the use of web-based learning media on student learning outcomes obtained from the analysis of hypothesis testing (2) there is a difference between student learning independence and student learning outcomes (3) there is no interaction between student learning independence and learning outcomes using web media.